CCBC Choices 2016 - Townsend, Emily McKnight; Schliesman, Megan; Lindgren, Merri V.; Horning, Kathleen T. (Friends of the CCBC, Inc., 2016)
CCBC CHOICES is an annual list of recommended books for children and young adults selected by the librarians at the Cooperative Children's Book Center, a library of the School of Education at the University of Wisconsin-Madison. CCBC CHOICES 2016 recommends 259 titles for children and young adults published in 2015. It includes a commentary on the 2015 publishing year, including statistics on the number of books by and about people of color and from First/Native Nations published for children and teens.
Keywords: multicultural literature; young adult literature; children's literature